Assessment of quality of life in children with epilepsy in Oman - Asia Alnaamani; Faraz Ahmad; Muna Al-Saadoon; Syed Gauhar Alam Rizvi; Amna Al-Futaisi (SpringerOpen, 2023)
Abstract Purpose The study aims to describe the quality of life (QoL) in Omani children with epilepsy at Sultan Qaboos University Hospital, Oman. Methods One hundred and one Omani children, with an age range from 5 to 18 years, diagnosed with epilepsy were enrolled in the study over 3 months. Descriptive epidemiology was used to characterize QoL in these children. QoL was measured using the PedsQL (4.0) questionnaire, a 23-item child and parent report questionnaire. Analysis of variance (ANOVA) was used to compare mean QoL scores, and agreement between the QoL reports of children and parents was evaluated using Spearman's rho; while, Multivariate analysis of variance (MANOVA) was performed to determine differences in subscale ratings. Results Factors affecting QoL included family status, income level, social security coverage, type of treatment, seizure frequency, age of onset, and seizure-free duration in years. Children between 5 and 7 years and females, in general, were most affected, as reflected by the overall QoL subscale. Consistency between the children's self-reports and parent proxy reports on the PedsQL™ was moderate to low. Conclusion Omani children with epilepsy have poor QoL, and their psychosocial function is severely affected. Therefore, QoL should be an important outcome measure in managing children with epilepsy rather than just seizure control.